Влияние типа опоры и передвижения на соотносительное развитие мышц плеча, действующих на локтевой сустав млекопитающих - Ковтун, М.Ф. (Вестник зоологии, 1973)
Data are presented on a relative weight of shoulder antagonistic muscles affecting the ulnar joint. The development degree of any limb muscle is shown to be determined first of all by the character and value of loading on this muscle. A change in loadings involves the muscle rearrangement. The similar rearrangement of muscles may be obtained by the effect of different factors. So, e. g. equalization of the ratio of the shoulder antagonistic muscles weight in various animals may occur, at least, in three ways; 1) as a result of relaxation of the group of extensors of the ulnar joint, when thoracic limbs to a greater or less extent lose the support function; 2) as a result of relaxation of a group of extensors with simultpneous intensification of flexors: 3) as a result of intensification of flexors without relaxation of extensors.